Penerapan Digital Learning Secara Synchronous danAsynchronoussebagai Alternatif Model Pembelajaran di Masa Pandemi untuk MeningkatkanKualitas Pembelajaran - Hendri, Jon (Universitas Batanghari Jambi, 2022)
Online learning during the Covid-19 pandemic has various constraint especially on Process and results less study _ satisfactory . Study this aim for increase ability student in understanding mathematics through approach asynchronous and synchronous using learning videos, Whatsapp, sheets work learners and Google meet. Study this belong to study action class. Subject the research is 20 student class XII MIPA 1. Study held in two cycles where stages at each the cycle is planning, implementation, observation and reflection. Instrument the research is plan implementation learning, observation sheet, sheet work students, videos, pretest questions and Posttest. Results study cycle I shows that the average score student in Cycle I 69 with a percentage of 65%. On cycle II, the average score student as big as 83with a percentage of 85%. So, deep online learning study this capable increase ability student in understand concepts and learning outcomes math.